Hospital Complications and Frailty in Mexican Older Adults: An Emergency Care Cohort Analysis - Pérez-Zepeda, Mario Ulises; Carrillo-Vega, María Fernanda; Theou, Olga; Jácome-Maldonado, Luis David; García-Peña, Carmen (Frontiers in Medicine, 2020)
Objectives. To describe the association of frailty level at Emergency Department (ED) with various hospital complications including delirium, low phase angle, and low handgrip strength. Design. Prospective cohort Setting. ED rooms of two public General Hospitals in Mexico City Participants. A total of 548 persons 60 years or older who were admitted to the ED and who were alive during follow-up testing at home were included. Measurements. A 32-item frailty index (FI) was measured at admission to the ED. Outcome measures included delirium, phase angle and hand grip strength measured during different stages of the hospitalization (i.e., from admission to the ED through follow-up at home). Results. From this final sample, mean age was 76 years (± SD 7.2) and 58.4% (n=320) were women. Mean waiting time in the ED was 5.1 hours (± SD 6.2), the average stay in the ED was 99.9 (±68.2) hours, and 274 subjects (50%) were admitted to a general ward after ED admission. FI was not associated with phase angle and negatively associated with handgrip strength at admission to ED (β=-3.97, confidence interval [CI] 95% -5.56 -2.38, p<.001), discharge from ED (β=-3.94, CI 95% -5.97 -1.90, p<.001) and discharge from hospital (β=-4.93, CI 95% -7.68 -2.18, p=0.01). FI was positively associated with delirium (β=3.68, CI 95% 1.53 - 5.83, p<0.01) Conclusion. Higher frailty at ED admission was associated with lower hand grip strength and delirium during hospitalization in Mexican older adults.